2020
DOI: 10.1016/j.ebiom.2020.102987
|View full text |Cite
|
Sign up to set email alerts
|

Modulating endothelial adhesion and migration impacts stem cell therapies efficacy

Abstract: Background Limited knowledge of stem cell therapies` mechanisms of action hampers their sustainable implementation into the clinic. Specifically, the interactions of transplanted stem cells with the host vasculature and its implications for their therapeutic efficacy are not elucidated. We tested whether adhesion receptors and chemokine receptors on stem cells can be functionally modulated, and consequently if such modulation may substantially affect therapeutically relevant stem cell interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Regarding the location of intravenously injected m17.ASC spheroids in the lung, it was reported that intravenously administered MSCs were found outside the blood vessels of the lung. [ 26 ] In addition, another report indicated that MSCs co‐cultured with vascular endothelial cells migrated underneath the vascular endothelial cells. [ 27 ] These reports suggest that intravenously injected MSCs adhere to the vascular endothelial cells of the blood vessels in the lung and migrate to the lung tissue from the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the location of intravenously injected m17.ASC spheroids in the lung, it was reported that intravenously administered MSCs were found outside the blood vessels of the lung. [ 26 ] In addition, another report indicated that MSCs co‐cultured with vascular endothelial cells migrated underneath the vascular endothelial cells. [ 27 ] These reports suggest that intravenously injected MSCs adhere to the vascular endothelial cells of the blood vessels in the lung and migrate to the lung tissue from the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the highest median doses have been given intravenously compared to other administration routes ( Kabat et al, 2020 ). Yet, it remains unclear if the known accumulation of MSCs in the lung after systemic application ( Kabat et al, 2020 ; Schäfer et al, 2020 ). is the rationale for such high-dose regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Surface proteins such as CD271, CD146, MSCA-1, CD106, CD119, CD140a, or distinct mRNA signatures, defining cell clusters within MSC preparations, could be assigned to MSC functions such as differentiation, tissue regeneration, immunomodulation, or wound healing ( Jones and Schäfer, 2015 ; Wu et al, 2016 ; Khong et al, 2019 ; Kuci et al, 2019 ). Moreover, MSC subpopulations’ motility and adhesion capacities can affect their therapeutic efficacy ( Danielyan et al, 2020 ; Schäfer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IV administration of PEI-MSCs in a rodent model increases homing rates to the brain and decreases the presence of PEI-MSCs in the lung vasculature. A cell’s ability to adhere and migrate within the local microenvironment influences therapeutic capabilities, as shown in a mouse glioblastoma model with non-PEI-MSCs conversely displays a heightened tumor migration [ 156 ]. Cell-free exosome therapy through the paracrine effect prevents difficulties when compared to cell therapies.…”
Section: Remodeling Of the Stroke Tissue Microenvironment Within The Brainmentioning
confidence: 99%